2017
DOI: 10.5455/ijlr.20170524115206
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Identification and Antibiogram of Bacterial Pathogens from Bovine Subclinical Mastitis in Asella, Ethiopia

Abstract: Mastitis, a disease complex of multiple etiologies, results into considerable financial losses to dairy industry worldwide. A cross sectional study was carried out between July 2013 to August 2013 in Asella town and its surrounding areas in order to cefotaxime, penicillin G, amoxicillin, ampicillin and vancomycin, which accounted 97.9%, 96.4%, 80.4%, 80.2% and 78%, respectively. Staphylococcus aureus revealed resistance against penicillin G, amoxacillin and tetracycline, which accounted 97.9%, 96.4% and 80.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
1
3
1
Order By: Relevance
“…The current study showed that the overall prevalence of mastitis in lactating cows was 54.9% of which the clinical and subclinical mastitis accounted for 2.9% and 52.1%, respectively. This study finding is relatively comparable with various reports from different parts of the country (Sori et al, 2005;Lakew et al, 2009;Abunna et al, 2013;Teklesilasie et al, 2014;Pal et al, 2017;Abebe et al, 2020). Subclinical mastitis was more prevalent (54.9% and 95% CI= 49.9-59.9) than clinical mastitis (2.9% and 95% CI= 1.6 -5.1) in the study area, which is in agreement with various studies reported from various parts of the country (Getaneh and Gebremedhin, 2017;Abebe et al, 2020;Fesseha et al, 2021;Belay et al, 2022;Demil et al, 2022;Girma and Tamir, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…The current study showed that the overall prevalence of mastitis in lactating cows was 54.9% of which the clinical and subclinical mastitis accounted for 2.9% and 52.1%, respectively. This study finding is relatively comparable with various reports from different parts of the country (Sori et al, 2005;Lakew et al, 2009;Abunna et al, 2013;Teklesilasie et al, 2014;Pal et al, 2017;Abebe et al, 2020). Subclinical mastitis was more prevalent (54.9% and 95% CI= 49.9-59.9) than clinical mastitis (2.9% and 95% CI= 1.6 -5.1) in the study area, which is in agreement with various studies reported from various parts of the country (Getaneh and Gebremedhin, 2017;Abebe et al, 2020;Fesseha et al, 2021;Belay et al, 2022;Demil et al, 2022;Girma and Tamir, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…The results were comparable to the ones found in Ethiopia [21] which found a prevalence of 61.1%. However, the results were lower than those reported in Nigeria (85.5%) [22], Ethiopia (72.7%) [23]. The reason for high SCM prevalence in the present study may be due to lack of proper mastitis control practices in the study area.…”
Section: Discussioncontrasting
confidence: 88%
“…The mean sample size of the 46 studies was 343 ± 165.4 cows. Among the 46 studies, three studies focused on estimating the prevalence and isolation of pathogens related to subclinical mastitis whereas the remaining studies included both types of bovine mastitis ( Pal, Lemu & Bilata, 2017 ; Mekonnen et al, 2017 ; Tegegne et al, 2020 ). Except for two studies, all studies performed a physical examination of the mammary gland and subsequent collection of milk samples for analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Except for two studies, all studies performed a physical examination of the mammary gland and subsequent collection of milk samples for analysis. Likewise, they have performed the California mastitis test and applied standard microbiological culturing techniques for the isolation of potential bacterial agents ( Pal, Lemu & Bilata, 2017 )( Birhanu et al, 2017 ). Concerning the regional states of study in the Ethiopia, 21 studies were from Oromia, 10 studies from SNNPR, five studies from Addis Ababa, four studies from Amhara, two studies from Somali, two studies from Dire Dawa and two studies from Tigray regional states ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%